Breath carbonyl compounds as biomarkers of lung cancer. Issue 1 (October 2015) - Li, Mingxiao; Yang, Dake; Brock, Guy; Knipp, Ralph J.; Bousamra, Michael; Nantz, Michael H.; Fu, Xiao-An
Highlights Classification models. Identified six biomarkers in exhaled breath. Threshold concentrations of biomarkers. Detection of early lung cancer.